Adsorbable organic halogens generation and reduction during degradation of phenol by UV radiation/sodium hypochlorite - Zeng, Qing-Fu (Water environment research : a research publication of the Water Environment Federation, 2009)
The degradation of phenol by UV radiation/sodium hypochlorite (UV/NaClO) was investigated. The degradation processes were analyzed by a UV-visible spectrometer, total organic carbon analyzer, and gas chromatography-mass spectroscopy. The experimental results indicate that phenol can be photodegraded by UV/NaClO effectively. However, adsorbable organic halogens (AOX) were produced during the degradation process. Analysis of the mechanism of degradation indicates that the decrease in pH value would increase the formation of AOX. Also, dissolved oxygen greatly increased the rate of phenol degradation and reduced the formation of AOX. Therefore, appropriate conditions could increase degradation and inhibit chlorination. Adjusting the pH value and increasing the amount of oxygen were effective methods